Amaiur Bendi - SiC Based Power Converter for Industrial Induction Hardening of Steel Probes - Bendi, Amaiur (Jornada de Jóvenes Investigadores del I3A, 2022)
SiC Based Power Converter for Industrial Induction Hardening of Steel Probes